If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -22 = -8y + 2(y + -8) Reorder the terms: -22 = -8y + 2(-8 + y) -22 = -8y + (-8 * 2 + y * 2) -22 = -8y + (-16 + 2y) Reorder the terms: -22 = -16 + -8y + 2y Combine like terms: -8y + 2y = -6y -22 = -16 + -6y Solving -22 = -16 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. -22 + 6y = -16 + -6y + 6y Combine like terms: -6y + 6y = 0 -22 + 6y = -16 + 0 -22 + 6y = -16 Add '22' to each side of the equation. -22 + 22 + 6y = -16 + 22 Combine like terms: -22 + 22 = 0 0 + 6y = -16 + 22 6y = -16 + 22 Combine like terms: -16 + 22 = 6 6y = 6 Divide each side by '6'. y = 1 Simplifying y = 1
| -7v+8=19 | | 8x-11=5x+1 | | 5(y-1)-5=45 | | -4(x+2)=4x+-8 | | -4(x+2)=4x+8 | | 7(2n-3)=5(3n-4) | | -17=4x-6 | | 10x+9=6x+25 | | 10x-22=68 | | x^2+x+2+x+2=100 | | x(x-5)=36 | | 4x^2-6x+2=0 | | 3(n+2)+4n=4(n+2)+4 | | 41+2(3x+6)=95 | | 2(3)-2(4x)+7=0 | | (2*a)+17= | | 3(n+2)-2=4(n-4)-4(n-11) | | 118-(3*b)= | | x(x-8)=-15 | | -3x^2+36x-72=0 | | 25x^2=100 | | 8(2x-1)=72 | | X+46=72 | | 5d-3.3=7.5 | | 17x-8x-9=76-40 | | n=15+2m-4 | | 5(3c-c)+3=43 | | (3x+2)(x+1)=4 | | 2w+9w+2w+8w+7w+w= | | 4a-2=7a-6 | | 6f+30=2f-8 | | 4(x+7.50)=40 |